2020
DOI: 10.1001/jamanetworkopen.2020.0643
|View full text |Cite
|
Sign up to set email alerts
|

Association of Disease Progression With Health-Related Quality of Life Among Adults With Breast, Lung, Pancreatic, and Colorectal Cancer

Abstract: IMPORTANCE Mortality, morbidity, and health-related quality of life (HRQoL) are patient-relevant end points generally considered in the early benefit assessments of new cancer treatments. Progression-related end points, such as time to progression or progression-free survival, are not included, although patients and physicians testify to the detrimental association of disease progression with HRQoL. OBJECTIVE To examine the association of disease progression and HRQoL in 4 prevalent solidcancer entities in rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 42 publications
(75 reference statements)
1
47
0
1
Order By: Relevance
“…Evidence indicates that disease progression is associated with a deterioration of QoL in this patient group. 85 There are also a number of other factors identified that may contribute to a worsening in QoL, such as treatments, comorbidities, and various demographic factors (including ethnicity, age, and educational level). 16 Although the benefits of exercise in QoL for various patients with cancer (including advanced disease) have been well established, 22 , 24 , 86 , 87 its effect for patients with PanCa requires further work and clarification.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicates that disease progression is associated with a deterioration of QoL in this patient group. 85 There are also a number of other factors identified that may contribute to a worsening in QoL, such as treatments, comorbidities, and various demographic factors (including ethnicity, age, and educational level). 16 Although the benefits of exercise in QoL for various patients with cancer (including advanced disease) have been well established, 22 , 24 , 86 , 87 its effect for patients with PanCa requires further work and clarification.…”
Section: Discussionmentioning
confidence: 99%
“…The staining sections were then reviewed and scored as follows by a pathologist with over 15 years of experience: Cells with <10% staining were scored as negative staining (−, 1); cells with 10-49% staining were scored as (+, 2); cells with 50-74% staining were scored as (++, 3); and cells with 75-100% staining were scored as (+++, 4). The staining color was scored as light-yellow particle ( 1 ), brown-yellow particle ( 2 ), and brown particle ( 3 ). The final score was defined as staining number score multiplied by staining color score ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…CRC progression, from adenoma to adenocarcinoma, is a multistep process ( 2 ). CRC results from a series of genetic and epigenetic alterations in key growth regulatory genes, which endow the colorectal cells with proliferative, survival, and metastatic advantages ( 3 ). The median overall survival (OS) of metastatic CRC (mCRC) is less than 3 years.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of progression-free survival has been shown across a variety of cancer types and is associated with a clinically relevant deterioration in quality of life. 36 For these reasons, the cost-effectiveness of withholding futile therapy for patients with KIT exon 9 variation is not surprising.…”
Section: Discussionmentioning
confidence: 99%